Glicerina na alimentação de cordeiros Ile de France em terminação - Merlim, Fernanda de Almeida [UNESP] (2015)
To assess if glycerin can properly substitute corn in sheep diets, 30 Ile de France lambs were confined, in individual pens, of 15.1 ± 0.146 kg to 32.2 ± 0.207 kg body weight, and fed with three diets containing sugarcane in natura as forage (50%) and concentrate (50%) without and with inclusion of 10 and 20% of glycerin in dry matter. Diets contained similar protein (16.72% of DM) and energy (3.86 Mcal/kg DM) levels. There were evaluated the performance, intake and apparent nutrient digestibility, apparent nitrogen balance, plasmatic glucose and insulin concentrations, urine formic acid concentration, in vitro gas production, in vivo and carcass morphological measures, quantitative parameters of the carcass and non-carcass components. Experimental design was completely randomized, and treatments compared by regression with the aid of SISVAR statistic program. Lambs fed with different diets had similar performance, with average daily weight gain of 0.239 kg, reaching final body weight usually at 73 ± 16 days of confinement. Increase of glycerin in diets reduced linearly the ingestion of ether extract and total carbohydrates, but had no effect on other nutrients consumption, with a decrease linear only in the apparent digestibility of ether extract, without affecting digestibility of other nutrients. Apparent nitrogen balance in lambs was positive in all three diets, with no significant difference, as well as plasmatic glucose and insulin concentrations, which were also similar. Urine formic acid concentration increased linearly 24.2% and 114.8%, respectively, with increased of glycerin level in diet for 10 and 20%, without signs of intoxication in lambs. In vitro gas production had linear reduction with increasing glycerin content in diet in all times assessed (24, 48 and 72 hours). Inclusions of 10 and 20% of glycerin in the diets promoted quadratic effect, with increase and reduction subsequent in rump width in vivo ...